Atomic, electronic and magnetic structure of an oxygen interstitial in neutron-irradiated Al2O3 single crystals - Seeman, Viktor O.; Lushchik, Aleksandr Ch; Shablonin, Evgeni; Prieditis, G.; Gryaznov, Denis; Platonenko, Alexander; Kotomin, Eugene A.; Popov, Anatoli I. (Nature Research, 2020)
A single radiation-induced superoxide ion O2- has been observed for the first time in metal oxides. This structural defect has been revealed in fast-neutron-irradiated (6.9×1018n/cm2) corundum (α-Al2O3) single crystals using the EPR method. Based on the angular dependence of the EPR lines at the magnetic field rotation in different planes and the determined g tensor components, it is shown that this hole-type O2- center (i) incorporates one regular and one interstitial oxygen atoms being stabilized by a trapped hole (S = 1/2), (ii) occupies one oxygen site in the (0001) plane being oriented along the a axis, and (iii) does not contain any other imperfection/defect in its immediate vicinity. The thermal stepwise annealing (observed via the EPR signal and corresponding optical absorption bands) of the O2- centers, caused by their destruction with release of a mobile ion (tentatively the oxygen ion with the formal charge −1), occurs at 500–750 K, simultaneously with the partial decay of single F-type centers (mostly with the EPR-active F+ centers). The obtained experimental results are in line with the superoxide defect configurations obtained via density functional theory (DFT) calculations employing the hybrid B3PW exchange-correlation functional. In particular, the DFT calculations confirm the O2- center spin S = 1/2, its orientation along the a axis. The O2- center is characterized by a short O–O bond length of 1.34 Å and different atomic charges and magnetic moments of the two oxygens. We emphasize the important role of atomic charges and magnetic moments analysis in order to identify the ground state configuration.
This work has been carried out within the framework of the EUROfusion Consortium and has received funding from the Euratom research and training programme 2014-2018 and 2019-2020 under Grant Agreement No. 633053 and Enabling Research project: ENR-MFE19.ISSP-UL-02 “Advanced experimental and theoretical analysis of defect evolution and structural disordering in optical and dielectric materials for fusion application”. The views and opinions expressed herein do not necessarily reflect those of the European Commission. In addition, the research leading to these results has received funding from the Estonian Research Council grant (PUT PRG619).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics